Rapid assessment of change and hurricane impacts to houston's Urban forest structure (2011)
A subsample of 332, 0.06-hectare plots measured during 2001–2002 in Houston, TX, U.S., were relocated and measured in 2008 following Hurricane Ike. These 37 re-measured plots provide a unique opportunity to explore the effects of urbanization and hurricanes on the forest structure of coastal urban forests. Statistical analyses of growth, mortality, and in-growth were conducted using plot- and tree-level factors. In total, 305 trees were re-measured, of which 195 (63.9%) still remained on-site and 110 (36.1%) had been removed. Ninety-seven (31.8%) of these trees were determined to be removed due to urbanization and 13 trees (4.3%) were removed due to hurricane impacts. Results show an overall annual net loss in tree numbers and an increase in tree density during the analysis period. Average annual mortality and in-growth rates were 3.9% and 5.3%, respectively. Growth rates were significantly influenced by land cover type, tree stem diameter, crown width, and percent dieback (P < 0.05). Overall, Hurricane Ike resulted in the removal of 4.3% of all trees measured, with removal occurring on six (16%) of the 37 re-measured plots. These initial findings could be used to understand changes in forest structure in coastal urban areas, improve estimates of carbon sequestration, and develop management goals.